EVALUATION ANALYSIS OF ISLAMIC RELIGIOUS EDUCATION (PAI) LEARNING IN THE SEMESTER CREDIT SYSTEM OF SMAN 1 PAMEKASAN - Syuhud, Ainus; Arif, Mahmud (Jurnal Ilmiah Didaktika, 2023)
To improve the quality of education, it is necessary to provide learning evaluations with a semester credit system to select students in the learning process. Therefore, this study aims to determine the application of the Semester Credit System (SKS) in Islamic Religious Education Learning and analyze the Implementation of PAI Learning Evaluation in the Semester Credit System at SMAN 1 Pamekasan. This research uses qualitative methods with a type of case study research. Data collection techniques use observation, interviews and documentation. While data analysis techniques go through the stages of data reduction, data presentation and conclusions. The results showed that face-to-face teaching, 1 hour of structured assignments, and 1 hour of independent activities, were delivered according to the principles of flexibility, excellence, continuous improvement, and equity. In contrast, the assessment of the credit system this semester uses the Model (IP) <2.66 -> 3.66.